MINNESOTA LEGISLATIVE OVERVIEW (Tufts Archival Research Center, 2007)
Minnesota Legislative Overview Report addressing the possibility of the Democrat Farm Labor Party losing its majority in Minnesota. Announces that all excise taxes are vulnerable to an increase. Comments on legislative efforts to dedicate cigarette and other excise tax to health, drug, and environmental programs. Emphasizes the importance of legislative efforts in Minnesota because of strong industry opposition. Indicates that the Tobacco industry's retail allies are interested in passing legislation that penalizes underage purchase of cigarettes.